2011
DOI: 10.1002/pon.1750
|View full text |Cite
|
Sign up to set email alerts
|

Survivor centrality among breast cancer survivors: implications for well‐being

Abstract: Objective-The goal of this research was to examine the extent to which 10-year breast cancer survivors integrated cancer into their self-concept (i.e., survivor centrality), identify predictors of survivor centrality, and determine the relation of survivor centrality to well-being.Methods-Breast cancer survivors (n = 240) were interviewed 10 years following the initial diagnosis. They completed measures of survivor centrality, illness valence (i.e., positive or negative views of illness), and well-being (posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 46 publications
9
38
1
2
Order By: Relevance
“…The meaning of survivorship may be based on a woman's age, life experiences, disease, ethnicity, or sociocultural background. While the literature is abundant with narratives of Caucasian breast cancer survivors (Documet, Trauth, Key, Flatt, & Jernigan, 2012;Helgeson, 2011;Morris, Campbell, Dwyer, Dunn, & Chambers, 2011;Pieters & Heilemann, 2011;Stanton et al, 2002), there remains a dearth of literature on AABCS. Pieters and Heilemann (2011) explored the concept of cancer survivor and cancer survivorship among 18 female breast cancer survivors from 70 to 94 years of age.…”
Section: Background/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The meaning of survivorship may be based on a woman's age, life experiences, disease, ethnicity, or sociocultural background. While the literature is abundant with narratives of Caucasian breast cancer survivors (Documet, Trauth, Key, Flatt, & Jernigan, 2012;Helgeson, 2011;Morris, Campbell, Dwyer, Dunn, & Chambers, 2011;Pieters & Heilemann, 2011;Stanton et al, 2002), there remains a dearth of literature on AABCS. Pieters and Heilemann (2011) explored the concept of cancer survivor and cancer survivorship among 18 female breast cancer survivors from 70 to 94 years of age.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…More important, they indicated that while survivorship is an individualized journey, nurses and other members of the health care team may need a better understanding of the definition of cancer survivorship and its meaning as a precursor to providing culturally competent care. Helgeson (2011) examined the concept of survivor centrality to determine if the meaning of cancer was central to the breast cancer survivors' identity. Survivors were asked to state how they saw themselves.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Além dos aspectos citados o tratamento antineoplásico por si só promove efeitos colaterais como fadiga, distresse, alteração da densidade mineral óssea, cardiotoxicidade, deficits cognitivos, medo de recorrência, infertilidade, linfedema, dentre outros (Siegel, Naishadham, & Jemal, 2013). Que podem ter repercussões físicas, como também psicossociais, e perdurar por meses e até anos após o fim do tratamento (Bower, & Lamkin, 2013;Goedendorp et al, 2012;Helgeson, 2013;Hofsø, Rustøen, Cooper, Bjordal, & Miaskowski, 2013;Kim, Barsevick, Beck, & Dudley, 2012;Lai, Garcia, Salsman, Rosenbloom, & Cella, 2012).…”
Section: Introductionunclassified
“…However, few studies have been designed to include women who have been diagnosed with breast cancer and analyze their perceptions of the breast cancer culture [25][26][27][28][29][30] . Even fewer studies have been focused on these women's feelings towards the term cancer survivor [12,31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…Of these three studies, Helgeson's [32] work was quantitative and was not designed to ask women open-ended questions about the term cancer survivor, whereas Document et al's [31] and Kaiser's [12] works were qualitative in nature and specific questions were asked of the women about their perceptions toward this term.…”
Section: Introductionmentioning
confidence: 99%